ANALISIS STURKTUR INTRINSIK DAN EKSTRINSIK NOVEL LITTLE WOMAN KARYA LOUISA MAY ALCOTT DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA - Evarita Aria Dedo; I Nyoman Suparsa; I Komang Widana Putra (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2022)
The background of the problem in this research is aimed at developing students' thinking power towards literary works in the world of fictional or non-viction stories including intrinsic elements and extrinsic elements in Louisa May Alcott's Little Woman novel and its implications in learning literature. Intrinsic elements include themes, characters, setting, plot, point of view and mandate, while extrinsic elements include the author's background and values contained in the novel. The method used in this research is the observation method while the data source used in this research is a novel entitled Little Woman by Louisa May Alcott. The results of the analysis show (1) themes: struggle for life, friendship and romance, (2) characters, (3) plot: plot structure using a forward plot that is told from the beginning to the end of the story, (4) setting: divided into three namely place, time , and atmosphere, (5) point of view: using a third person point of view (name of person), (6) message: the message conveyed in the novel Little Woman by the author to the reader. While extrinsic elements include (1) the author's background and the values contained (moral, social, cultural, religious, and educational values). The implication of the Little Woman novel in learning literature is that this research can be used as a reference for students in analyzing a novel about the intrinsic and extrinsic elements contained in it.